The Perceptions and Risk Reduction Strategies of Small-Scale Salt Farmers on Madura Island - Elys Fauziyah; Wenchi Huang; Setiani Setiani; Nur Qomariyah; Ika Fatmawati (Institut Pertanian Bogor, 2024)
Salt farming is considered a risky venture due to the influence of both internal and external factors. Therefore, this study aimed to describe farmers' perceptions regarding the causes, opportunities, and impacts of risks to develop a risk reduction strategy for salt farming in Madura Island. The study used a multistage sampling method to obtain 120 respondents and was conducted in three regencies: Sampang, Pamekasan, and Sumenep. The first objective was analyzed using the descriptive method, while the second was designed using the Kountur method. Farmers' perceptions showed that seawater quality, wind and temperature, rainfall, soil porosity, price volatility, marketing channels, government policies, capital constraints, and human resource quality could cause risks in salt farming. Several risks were perceived to significantly impact salt farming, such as government policies, partnerships, marketing channels, prices, and capital availability. Therefore, some recommendations to improve the risk reduction strategies included the use of horizontal axis windmills, revitalization of groups and partnerships, and capital strengthening through the effectiveness of the PUGAR (Empowerment of Smallholder Salt Businesses) policy by the development of standard procedures for the timely and targeted distribution of the aides. Keywords: perception, risk, salt, strategy